PENGARUH REVITALISASI TAMAN KOTA KUNINGAN TERHADAP KENYAMANAN FISIK MASYARAKAT - Efendi, Angga Kusuma; Amelia, Siska (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
A city park that functions as a public space, in the middle of routine. making thislocation busy with many people. People come to do different activities, for examplesome just read a book while sitting under a tree, jogging, and maybe some come to thecity park on a mission to trade. City parks as public spaces are containers where socialinteraction occurs (Carmona, 2003).Kuningan City Park is one of the parks in Kuningan city which was built in 2008.This place exists as a place for relaxation and recreation for the community. As one ofthe recreation areas in Kuningan citr, people certainly have preferences regardingKuningan City Park. This research aims to determine people's preferences for thephysical comfort of Kuningan City Park after renovations which cost quite a lot ofmoney.